The Analysis of the Household Wastewater Sewerage Ownership Factor in the Working Area of Pamotan Health Center, Rembang Regency, Central Java - Kholifah Maulidya Arsanata; Eram Tunggul Pawenang (Jurnal Presipitasi : Media Komunikasi dan Pengembangan Teknik Lingkungan, 2024)
Households with access to wastewater sewerage in Pamotan in 2022 only be 69.9%. This study aims to find out the factors related to household wastewater sewerage ownership in the Pamotan Community Health Center Working Area. This research was an observational analytic using a cross-sectional design. The research population was all families in Pamotan subdistrict villages with the lowest ownership of wastewater sewerage, with a sample size of 90 families. The independent variables are land availability, length of year residence, knowledge, education, and income for the dependent variable, that are ownership of the Waste Water Sewerage. The data were analyzed using univariate and bivariate statistics, employing the Chi-Square test. The results of the study showed that land availability (p=0.04), education level (p=0.018), knowledge level (p=0.003), and income (p=0.00) are related to household wastewater disposal ownership while the length of year residence (p=0.257) is not related to ownership of household wastewater sewerage in the Pamotan Subdistrict. Based on the research results, the length of year residence is not related to household wastewater sewerage ownership because people's old habits that are not good at managing household wastewater result in wastewater sewerage ownership behavior not fulfilling standards.